STUDI TENTANG IKLIM ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KSP BINA SEJAHTERA - ANGELIKA, WANDA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study aims to find out how the organizational climate and the implementation of Organizational Citizenship Behavior (OCB), as well as the factors that influence both aspects of the KSP Bina Sejahtera. This research is a type of qualitative research that is descriptive. Data sources come from observation and in-depth interviews. The data analysis technique used is interactive analysis of Milles and Hubberman, where data is collected, presented, reduced, and drawn conclusions. The results show that a good organizational climate and the application of Organizational Citizenship Behavior (OCB) are very important for the progress of an organization because it has influence on increasing maximum performance. In addition, the organizational climate influences the creation of OCB actions carried out by employees, because the organizational climate is an initial condition that triggers OCB. When the organizational climate is good, the members of the organization will always support the work beyond the obligations they should and will always support the goals of the organization.